تأثير تقنيات المعلومات على مهنة المكتبات - خالد نوري عبدالله (PROSPECTIVE RESEARCHES, 2023)
The aim of this study is to identify amount moment the situation of the branch libraries of the Northern Technical University، as well as to identify the scope of effect of information technology on the staff of libraries in the colleges and institutes of the University. The study was applied on nine academic libraries of the colleges and Institutes of the University. This study used the descriptive analytical method depending on a questionnaire in collecting the data in addition to the field visits for the libraries under study. The study reached several results among them are: The number of computers available in university formations libraries is less than required and does not meet the need، and the lack of all libraries of the existence of automated systems or the Internet network or subscription to databases. The research recommended the necessity of libraries to the latest developments and the application of technology in their optimal form.